Diversity of the Board of Directors and Company Financial Performance in the Perspective of Good Corporate Governance - Ridloah, Siti; Noekent, Vitradesie; Putri, Vini Wiratno; Waliuddin, Achmad Nauval (Management Analysis Journal, 2022)
Companies with diverse boards provide various resources to the organization. The existence of good governance will result in good decisions as well, thus directing the company in generating high profits. This study aims to analyze the effect of board of directors diversity on the company's financial performance (ROA).This study develops and focuses on the variables of gender, nationality, age, education, and independent commissioner as variables that describe the diversity of the board. This study uses a quantitative approach with secondary data sources. The population used is banking sector companies listed on the Indonesia Stock Exchange for the 2009-2019 period. The sampling technique used purposive sampling method. The data analysis used is multiple linear regression. Based on data analysis, the results obtained that national diversity and educational diversity have a significant effect on the company's financial performance. Meanwhile, gender diversity, age diversity and the existence of independent commissioners have no significant effect on financial performance. Simultaneously, gender diversity, nationality diversity, age diversity, education diversity and the existence of independent commissioners have a significant effect on the company's financial performance